1968
DOI: 10.1063/1.1656791
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Phonon Attenuation in Magnesium Aluminate Spinel

Abstract: Articles you may be interested inA microwave resonator for limiting depth sensitivity for electron paramagnetic resonance spectroscopy of surfaces Rev. Sci. Instrum. 85, 104707 (2014); 10.1063/1.4898179 Strong asymmetrical doping properties of spinel CoAl2O4Measurements are reported of the attenuation of microwave phonons of various modes in magnesium aluminate spinel (MgAbO,). The attenuation of certain modes is lower than in any other material measured and permits the observation of 9000 MHz echo patterns at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1969
1969
2009
2009

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…This value is a factor of 2 lower than that for any other longitudinal mode reported, and it is comparable to the value found for shear waves propagating along the [100] axis of flux-grown spinel. 19, 20 We conclude that f:l-boron is a material with low acoustic losses, as predicted,6,7 and that further investigations of the attenuation of various ultrasonic modes in boron polymorphs or icosahedral boron compounds should show similar low-loss behavior.…”
Section: Temperature and Frequency Dependence Of Microwave Elastic Lomentioning
confidence: 61%
“…This value is a factor of 2 lower than that for any other longitudinal mode reported, and it is comparable to the value found for shear waves propagating along the [100] axis of flux-grown spinel. 19, 20 We conclude that f:l-boron is a material with low acoustic losses, as predicted,6,7 and that further investigations of the attenuation of various ultrasonic modes in boron polymorphs or icosahedral boron compounds should show similar low-loss behavior.…”
Section: Temperature and Frequency Dependence Of Microwave Elastic Lomentioning
confidence: 61%
“…The values of the attenuation at 78K of the acoustic waves in spinel and lithium niobate are presented in the Table 1. For spinel in accordance with [6] at the increase of the temperature from 78 up to 170 K the value of ωτ (ω = angular frequency of wave, τ = average relaxation time of the thermal phonons) passes from the value >1 to the value ~1. For lithium niobate ωτ ≈1 [26].…”
Section: The Investigations Of the Acoustic Waves Of The Frequenmentioning
confidence: 70%
“…At first quartz, cadmium sulfide, ruby, magnesium oxide, and lithium niobate were investigated at low temperatures <150К [1][2][3]. Then the data about the attenuation of the acoustic waves up to the 300K in such crystals as ruby, lithium niobate, topaz, magnesium aluminate spinel (spinel), tourmaline, yttriumaluminum garnet, diamond, and silicon carbide was published in [4][5][6][7][8][9][10][11][12][13][14][15]. It was found that the minimum attenuation exists in diamond [13] for the longitudinal waves and in spinel [6][7][8][9][10] and in yttrium-aluminum garnet [11][12] for the shear waves.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the normal spinels the X ions (0, S, Se) form a slightly distorted cubic close-packed structure with 1/8 of the octahedral and 1/2 of the tetrahedral interstices occupied by B ions (Al, Cr, Ga) and A ions (Mg, Zn, Fe, Co, Ni), respectively [ 11. Among the most outstanding physical properties are the ferrimagnetic behaviour of the ferrite spinels with applications as magnetic high-frequency core materials [2], and the unusually low high-frequency ultrasonic attenuation of MgA1,0, with potential applications in passive ultrasonic delay lines [3]. The ultrasonic attenuation behaviour is closely related to the elastic and thermal properties of these spinels and, therefore, in this note a thermal property, i.e.…”
mentioning
confidence: 99%